Estudo de adobes melhorados com cimento e adição de resíduos de concreto - Couto, Caroline Rezende [UNESP] (2013)
In view of current preoccupation with ecologic buildings right, the adobe comes as an important choice in low cost edifications, because it saves on transportation when the appropriate land is found in the same place that the work; doesn´t require skilled labor; has excellent thermal comfort; and doesn’t consume energy to production. It´s a millennial construction material, very used in many parts of the world. The raw material necessary to production of adobe is land and water, found easily in the nature. Besides that, it has low energy cost, the manufacture process is simple and doesn´t need baking, being considered an appropriate technology with sustainability concept. In this research, it evaluated the production of adobes with addition of cement and construction waste. Material characterization tests were performed, including particle size analysis, determination of density in loose condition and consistency limits. The tests with the adobe, with dimensions of 7,5 cm x 15 cm x 30 cm, were out specific mass, linear shrinkage, hygroscopic moisture, absorption and mechanical resistance to compression. To improve the homogenization proceeded to the mixture of components in a concrete mixer, resulting in a material of plastic consistency. Curing was done in a humid at 7, 28 and 56 days chamber. It was concluded that the addition of concrete residue contributed to promote a trend of increased resistance, reduced absorption and linear shrinkage. The addition of cement promoted an increase in resistance as a function of time and decreased absorption.